Rare Association of Anti-Hu Antibody Positive Paraneoplastic Neurological Syndrome and Transitional Cell Bladder Carcinoma - S. Lukacs; N. Szabo; S. Woodhams (Case Reports in Urology)
Introduction. Paraneoplastic encephalomyelitis (PEM) and subacute sensory neuronopathy (SSN) are remote effects of cancer, usually associated with small-cell lung carcinoma and positive anti-Hu antibody. We describe the rare association of bladder transitional cell carcinoma (TCC) with anti-Hu antibody positivity resulting in this paraneoplastic neurological syndrome. Patient. A 76-year-old female presented with bilateral muscle weakness and paraesthesia of the upper and lower limbs in a length-dependent “glove and stocking” distribution. Central nervous system symptoms included cognitive problems, personality change, and truncal ataxia. Case notes and the literature were reviewed. Result. Autoantibody screening was positive for anti-Hu antibody (recently renamed antineuronal nuclear antibody 1, ANNA-1). The diagnosis of PEM and SSN was supported by MRI and lumbar puncture results. A superficial bladder TCC was demonstrated on CT and subsequently confirmed on histology. No other primary neoplasm was found on full-body imaging. The neurological symptoms were considered to be an antibody-mediated paraneoplastic neurological syndrome and improved after resection of the tumour. Discussion. The association of anti-Hu positive paraneoplastic neurological syndrome and TCC has not been described in the literature previously. We emphasize the need for detailed clinical examination and the importance of a multidisciplinary thought process and encourage further awareness of this rare association.